RESTRUCTURING KIDNEYS IN EXPERIMENTAL DIABETES MELLITUS AND ATHEROSCLEROSIS - Beloshitsky, O.V.; Fedorchenko, V.A.; Beloshitsky, V.V.; Білошицька, Ж.Л.В. (World of Medicine and Biology, 2015)
Studied the histological structure of rat kidneys with the eksperimental atherosclerosis and diabetes. Founded pathological changes in the structure of the nephron in rats with the pathology models.
Keywords: atherosclerosis; diabetes; rat kidneys